Instructional leadership and teacher professional learning in Chinese calligraphy education: The moderating role of employment status - Xinkun Xie; Bity Salwana Alias; Mohamed Yusoff Mohd Nor (Environment and Social Psychology, 2026)
In the context of Chinese calligraphy education, this study investigates how principals' instructional leadership influences teacher professional learning. Based on survey data from 483 calligraphy teachers and based on social cognitive theory, the results show that in subjects with poorly institutionalised professional learning systems, instructional leadership serves more as a source of organisational meaning and support than as a technical management mechanism. In order to maintain teachers' learning engagement, leadership methods focused on fostering a healthy school climate and communicating instructional value are especially important. Crucially, the study shows that rather than being consistent, leadership impacts are structurally contingent. The link between instructional leadership and teacher professional learning is highly moderated by employment status, with full-time teachers reacting more strongly to leadership support because of their greater organisational embeddedness and more reliable access to school-based resources. This demonstrates how teachers' ability to translate leadership cues into ongoing professional development is shaped by employment frameworks. This study expands instructional leadership and teacher professional learning theory beyond core topics by emphasising the idea of subject ecology, which is characterised by curricular marginality, unequal resource allocation, and employment precarity. It emphasises how organisational settings and employment arrangements may support or restrict teacher agency and learning opportunities in disadvantaged educational areas, in addition to the leadership practices themselves.